Inhibitory effect of ethanolic extract of propolis on corrosion of ferritic stainless steel in chloride media - Dolabella, Luiza Marilac Pereira (Array, 2019)
This work evaluates the inhibitory effect of ethanolic extract of propolis (EEP) on the corrosion of AISI 409 stainless steel (SS) in chloride media. Additions of 100, 200, and 500 μL of EEP in an aqueous sodium chloride solution were performed. The inhibitory effect on the SS was evaluated using electrochemical impedance spectroscopy (EIS) measurements up to 720 hours in immersion. EEP additions of 200 μL and 500 μL increased the polarization resistance of the SS. After 720 hours of immersion, the highest impedance was identified for the SS in solution with 500 μL of EEP. The maximum inhibition efficiency observed for addition of 500 μL of EEP in solution was 98.1 %, after 360 h of immersion.